Micheál Breathnach - Mac Domhnaill, Tomás,Mac Énrí, Seán,Ó Tuairisg, Lochlainn (Cló lar-Chonnacht, 2009)
Mícheál Breathnach was a writer from Cois Fharraige in Connemara who dies in 1908 at the young age of twenty seven.
Description based on publisher supplied metadata and other sources